Development of proteomic technique for potential species-specific peptide marker discovery of commercial seasoning cubes - Mohd Asri, Ummu Nasuha (2020)
Recent years, concerns regarding food product authentication particularly in meat-based product has been alarming. The development of proteomic technique in food authentication and their application to determine quality and safety issues of the ingredients has been progressively investigated by fellow researchers. The complexity of matrices in commercial seasoning cubes have given challenge in developing authentication method. Hence, the present study has been carried on developing protein extraction method on commercial seasoning cubes and generates electrophoretic profiles of chicken, beef, pork and anchovies commercial seasoning cubes and also to determine potential species-specific peptide marker in the commercial seasoning cubes using LC MS/MS analysis. Four flavors of seasoning cubes (Chicken, Beef, Anchovies and Pork) from three brands (T, K and M) were purchased. The efficacy of urea-thiourea extraction was studied using concentration of extracted protein from seasoning cubes. The electrophoretic profile of seasoning cubes of different species was analyzed using SDS-PAGE combined with principle component analysis (PCA). LC MS/MS analysis was developed to identify species-specific peptide markers in commercial seasoning cubes. Finding shows, the efficacy of urea-thiourea solvent extraction on commercial seasoning cubes was depending on species. Based on electrophoretic profile combined with PCA, seasoning cubes of four (flavors) species share similar protein molecular weight and group closely together. In this study, two porcine-specific peptide markers derived from hemoglobin subunit α and β, respectively have been successfully identified in pork commercial seasoning cubes. Also, one bovine-specific peptide marker derived from hemoglobin subunit α has been successfully identified in beef commercial seasoning cube. Meanwhile, two actinoperygii (bony fish)-specific peptide marker were identified in anchovies commercial seasoning cube and one aves (bird)-specific peptide marker was identified in chicken commercial seasoning cube. The methodology developed in this study has been proved to be successful in identifying species-specific peptide markers in seasoning cubes. Findings from this study can be a reference in validating of food authenticity especially in commercial seasoning products.